THE DEFINITION OF RATIONAL ALLOCATION OF TRAIN-FLOWS ON THE RAIL NETWORK - Kurgan, D. M.; Zayats, M. A. (Science and Transport Progress, 2010)
A technique of rational distribution of train traffic streams on the system of railways by a few indices is presented.